2008
DOI: 10.1002/jpln.200700317
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of climate‐relevant trace gases between a Norway spruce forest soil and atmosphere during repeated freeze–thaw cycles in mesocosms

Abstract: For this century, an increasing frequency of extreme meteorological boundary conditions is expected, presumably resulting in a changing frequency of freezing and thawing of soils in higher‐elevation areas. Our current knowledge about the effects of these events on trace‐gas emissions from soils is scarce. In this study, the effects of freeze–thaw events on the fluxes of the trace gases CO2, N2O, and NO between soil and atmosphere were investigated in a laboratory experiment. Undisturbed soil columns were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 48 publications
6
37
0
Order By: Relevance
“…In the present study, increased soil CO 2 emissions during FTCs have been found in both watering and snow cover treatments, which is in agreement with previous observations in various ecosystems (Koponen and Martikainen 2004;Goldberg et al 2008;Wu et al 2010a, b;Kim et al 2012). Stimulation of microbial metabolisms by enhanced substrate supply and physical mechanisms have been commonly considered as the reasons for these emission pulses (Priemé and Christensen 2001;Matzner and Borken 2008;De Bruijn et al 2009).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, increased soil CO 2 emissions during FTCs have been found in both watering and snow cover treatments, which is in agreement with previous observations in various ecosystems (Koponen and Martikainen 2004;Goldberg et al 2008;Wu et al 2010a, b;Kim et al 2012). Stimulation of microbial metabolisms by enhanced substrate supply and physical mechanisms have been commonly considered as the reasons for these emission pulses (Priemé and Christensen 2001;Matzner and Borken 2008;De Bruijn et al 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Stimulation of microbial metabolisms by enhanced substrate supply and physical mechanisms have been commonly considered as the reasons for these emission pulses (Priemé and Christensen 2001;Matzner and Borken 2008;De Bruijn et al 2009). In both watering and snow cover treatments, CO 2 emissions were highest in the first thawing cycle and decreased in following cycles, indicating that repeated FTCs might have considerable effects on microbial activity/population and labile substrate pools (Priemé and Christensen 2001;Goldberg et al 2008). .05, **P <0.001 (significance levels) a Soil gas concentration differences were calculated from the concentration of the lower sampling depth minus the concentration of the upper sampling depth Such a decrease of the initial CO 2 emissions during repeated FTCs has not only been reported in laboratory studies (Priemé and Christensen 2001;Koponen and Martikainen 2004), but also in several field observations (Holst et al 2008;Wu et al 2010b), which suggests that adjusting soil moisture by watering before soil freezing might not lead to significant differences in the CO 2 emission pattern during FTCs as compared to natural snow cover conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the absence of peak flux in the field observation, the incipient rates of N 2 O and CO 2 fluxes calculated in this study (Figs 2 and 4) would be appropriate to represent the magnitude of N 2 O and CO 2 flush fluxes following spring soil thawing. From the results of this present study and previous studies, it can be reasonably concluded that an increase in soil moisture can delay the appearance of N 2 O and CO 2 peak fluxes from thawing soils and their maximum fluxes vary with different soil types, which depends on soil moisture, freeze-thaw conditions, and the substrates supplied (Goldberg et al, 2008;Kim et al, 2012;Sehy et al, 2004;Vilain et al, 2010). Without C and N addition, the concentration of NO 3 --N in BKPF soil with high moisture remained at 0.77 g N m -2 at the end of incubation (Supplementary Table S3).…”
Section: Discussionsupporting
confidence: 77%
“…These released substrates can be utilized during nitrification, denitrification, and microbial respiration processes and thus may promote nitrous oxide (N 2 O) and carbon dioxide (CO 2 ) fluxes from soils during spring thaw (Mørkved et al, 2006;Goldberg et al, 2008;Wu et al, 2010). However, no pulse of CO 2 fluxes occurred during autumn and spring freeze-thaw periods in field experiments (Rong et al, 2015) and the stimulus degree of freezing-thawing events on soil N 2 O and CO 2 fluxes varies greatly among recent studies (Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%